The Use of Arbitration Mechanisms to Resolve Business Disputes Outside the Formal Justice System - Djuanda, Dede Hendratno; Hartono, Suwandi; Aziz, Miftah; Harmono, Harmono; Fathurohman, Dadan Taufik (Indonesian Journal of Advanced Research, 2025)
This study evaluates the effectiveness of arbitration in resolving business disputes compared to formal judicial channels, and analyzes the legal force of arbitral awards. In the competitive business world, conflicts often occur, and resolution through the courts is considered less efficient because it is time-consuming, high cost, and open to the public. Arbitration as a form of Alternative Dispute Resolution (ADR) offers a fast, flexible, closed process, and a binding award. In Indonesia, this mechanism is regulated in Law No. 30 of 1999 and is implemented by institutions such as BANI and Basyarnas. A normative juridical research method was used. Challenges still exist, such as lack of understanding and execution of court-dependent decisions.